THE UTILIZATION OF A READING CORNER IN IMPROVING STUDENTS’ READING INTEREST AT MI MIFTAHUL ULUM BANYUPUTIH KIDUL - Ainul Rohmah, Hikmatul; Zainal (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to describe the utilization of a reading corner in improving students’ reading interest at MI Miftahul Ulum Banyuputih Kidul. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, teachers, and three students. Data were collected through observation, interviews, and documentation, while data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. Data validity was tested through source triangulation. The findings revealed that the utilization of the reading corner played an effective role in improving students’ reading interest. This was indicated by the increased enthusiasm of students in reading activities, their habit of using spare time for reading, and their active participation in reading habituation activities before the learning process began. This success was supported by an attractive reading corner design, a clean and comfortable environment, a diverse collection of books, as well as support from teachers and the principal in managing literacy programs. In addition to functioning as a literacy support facility, the reading corner was also utilized as an alternative learning resource and a medium for character building, such as discipline, responsibility, and independent learning habits. Therefore, the reading corner can be considered an effective literacy strategy in fostering a reading culture and improving the quality of learning in Islamic elementary school settings.